JavaScript DOM interactive and dynamic JavaScript - Svekis, Laurence (Packt Publishing, 2019)
"Create Dynamic and interactive web pages with JavaScript and the DOM. In this course, you will learn how to make web-pages dynamic and interactive using JavaScript to connect with the Document Object Model and influence and manipulate page elements. The Document Object Model is a massive object that represents your page elements and their attributes. JavaScript can easily select objects within the DOM and use their content to change the display, add interactive events, update styling, and a whole lot more. JavaScript makes your web page come to life; it opens doors and makes amazing things happen on your website. This course covers only the JavaScript Document Object Model and prior JavaScript knowledge is a prerequisite."--Resource description page
Title from resource description page (Safari, viewed March 8, 2019)
Keywords: JavaScript (Computer program language); Web site development; Web sites -- Design; JavaScript (Langage de programmation); Sites Web; Développement; Sites Web; Conception; Web sites; Design